Geosynthetic-reinforced pile-supported embankments − 3D discrete numerical analyses of the interaction and mobilization mechanisms. (1st September 2021) - Pham, Tuan A.; Tran, Quoc-Anh; Villard, Pascal; Dias, Daniel
Highlights: Subsoil provides a substantial support and reduces the reinforcement tension. Design guideline CUR226 and standard EBGEO agree well with the numerical results. 3D Numerical discrete analysis and comparison with analytical models. Abstract: Three-dimensional numerical analyses using the discrete element method are conducted to investigate several fundamental aspects related to soil-structure interaction and mobilization mechanisms in the geosynthetic-reinforced and pile-supported embankments. The contributions of the soil arching, tensioned membrane effect, friction interaction, subsoil support, and punching failure are investigated. The results indicated that the inclusion of the geosynthetic enhances the stress transfer from the subsoil to piles due to the tensioned membrane action, and the stress distribution is more uniform as compared to piled embankment without geosynthetic. However, the tension distribution in geosynthetic is not uniform and the maximum tension occurs near the pile edge. Numerical results also proved that the subsoil provides substantial support and reduces the reinforcement tension while shear stresses are mobilized along the upper and lower sides of soil-geosynthetic interfaces. These mechanisms should be considered in theoretical models to produce a more realistic approach. Finally, ten available design methods are reviewed and compared to the numerical results to assess the performance of analytical models. The results showed that the design method of Pham, CUR 226 design guideline, and EBGEO design standard agree well with the numerical results and are generally better than the results of all other methods.